PSYCHOLOGICAL INTERVENTION WITH PARENTS OF AUTISTIC CHILDREN - Malhotra, S. (Medknow Publications, 2002)
An important component of management of autism is the role played by parents as active collaborators in the process. The case histories of 5 children with autism are described in this report. Psychological intervention carried out with parents of these children is detailed. The treatment package included a mix of behavioural, supportive and educational techniques, delivered in 3-6 sessions of 45- 60 minute each, in the setting of a child psychiatric clinic. Results showed that on the whole parents found this brief contact helpful. They rated emotional aspects of the support offered to be the most helpful. Child psychiatric clinics are often the first point of contact for parents with autistic children, and may have an important, primarily supportive role to play at this early stage of treatment.